Dalihan Na Tolu Analogy as an Approach to Strengthen Men’s Ministry Role - Rapina Ina Buana Habeahan; Iky Sumarthina P. Prayitno (Evangelikal: Jurnal Teologi Injili dan Pembinaan Warga Jemaat, 2022)
Of all categorical ministry, men’s ministry are not as actively involved in the church ministry as others do. This article discusses the ways to strengthen men’s ministry role in the Batak Protestant Christian Church (HKBP) in present day through cultural approach. The research used cultural analogy approach. Data were collected by using observation and interviews. In analyzing the data, the researcher employed relevant literature sources such as books and journal articles. The research shows that the elements of Batak principles of Dalihan Na Tolu upholding a Batak person and his/her families of Hula-hula, Dongan Tubu, and Boru were found to be still relevant. The principle’s framework could be used as an approach to strengthen role of male church parishioners in the church by associating it with another three elements: the Church, Bibel (the Bible), and the family. Thus, Dalihan Na Tolu as a cultural principle is applicable to church ministry setting by association of: (1) the organized Church to Hula-hula, (2) the family to Boru, and (3) Bibel as Dongan Tubu